Dose Rationalization of Pembrolizumab and Nivolumab Using Pharmacokinetic Modeling and Simulation and Cost Analysis. Issue 4 (16th October 2017) - Ogungbenro, Kayode; Patel, Alkesh; Duncombe, Robert; Nuttall, Richard; Clark, James; Lorigan, Paul
Abstract : Pembrolizumab and nivolumab are highly selective anti‐programmed cell death 1 (PD‐1) antibodies approved for the treatment of advanced malignancies. Variable exposure and significant wastage have been associated with body size dosing of monoclonal antibodies (mAbs). The following dosing strategies were evaluated using simulations: body weight, dose banding, fixed dose, and pharmacokinetic (PK)‐based methods. The relative cost to body weight dosing for band, fixed 150 mg and 200 mg, and PK‐derived strategies were –15%, –25%, + 7%, and –16% for pembrolizumab and –8%, –6%, and –10% for band, fixed, and PK‐derived strategies for nivolumab, respectively. Relative to mg/kg doses, the median exposures were –1.0%, –4.6%, + 27.1%, and +3.0% for band, fixed 150 mg, fixed 200 mg, and PK‐derived strategies, respectively, for pembrolizumab and –3.1%, + 1.9%, and +1.4% for band, fixed 240 mg, and PK‐derived strategies, respectively, for nivolumab. Significant wastage can be reduced by alternative dosing strategies without compromising exposure and efficacy.